2006
DOI: 10.1002/hup.800
|View full text |Cite
|
Sign up to set email alerts
|

Verbal memory performance during subchronic challenge with a selective serotonergic and a mixed action antidepressant

Abstract: Verbal memory was not affected by acute and subchronic escitalopram treatment in healthy participants. Overall immediate verbal memory was slightly but significantly impaired throughout mirtazapine treatment, probably due to a general reduction in overall arousal caused by H1 blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…In a small study ( N = 18) in healthy individuals, verbal memory was impaired with acute (2 days and 9 days) and subchronic (16 days) treatment with mirtazapine 30–45 mg/d. Escitalopram 10–20 mg did not affect verbal memory in this placebo-controlled cross-over study (Wingen et al, 2006). However, adjunctive mirtazapine may enhance cognition in patients with schizophrenia (Cho et al, 2011; Stenberg et al, 2010, 2011).…”
Section: Serotonin Receptors and Cognition – Data From Animal And Hummentioning
confidence: 77%
“…In a small study ( N = 18) in healthy individuals, verbal memory was impaired with acute (2 days and 9 days) and subchronic (16 days) treatment with mirtazapine 30–45 mg/d. Escitalopram 10–20 mg did not affect verbal memory in this placebo-controlled cross-over study (Wingen et al, 2006). However, adjunctive mirtazapine may enhance cognition in patients with schizophrenia (Cho et al, 2011; Stenberg et al, 2010, 2011).…”
Section: Serotonin Receptors and Cognition – Data From Animal And Hummentioning
confidence: 77%
“…A range of studies have demonstrated that these drugs produce subjective fatigue and sleepiness and impair psychomotor function, cognition, and actual driving performance after acute dosing and to a lesser degree as well as after repeated dosing (Curran et al 1986; Mattila et al 1989; Ramaekers 2003; Ramaekers et al 1998; 1992; Ridout et al 2003; Wingen et al 2005; 2006). Several studies have demonstrated that mirtazapine increases sleep efficiency, total sleep time, and slow wave sleep in patients with major depressive disorder and in healthy subjects (Anttila and Leinonen 2001; Radhakishun et al 2000; Ruigt et al 1990; Schmid et al 2006; Winokur et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, concerning the effect of SSRIs in healthy individuals, 18 randomized trials using 39 different neuropsychological tests to investigate cognitive function were identified [Knorr and Kessing, 2010]. Treatment with a SSRI was found to improve [Murphy et al 2008;Loubinoux et al 2005;Harmer et al 2004;Schmitt et al 2001;Knutson et al 1998Knutson et al , 1997, deteriorate [Riedel et al 2005;Schmitt et al 2002aSchmitt et al , 2001Fairweather et al 1997;Ramaekers et al 1995;Robbe and O'Hanlon, 1995] or have no effect on cognitive function [Peran et al 2008;Paul et al 2007Paul et al , 2002Wingen et al 2006Wingen et al , 2005Loubinoux et al 2005;Riedel et al 2005;Siepmann et al 2003;Schmitt et al 2002aSchmitt et al , 2002bSchmitt et al , 2001Wilson et al 2002;Allen et al 1988;Fairweather et al 1997;Ramaekers et al 1995;Robbe and O'Hanlon, 1995]. It was concluded that the diverging findings could be a result of a number of methodological drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…Two of these studies found no significant effect of escitalopram. Wingen and coworkers [Knorr and Kessing, 2010;Wingen et al 2005Wingen et al , 2006 investigated doses of escitalopram 1020 mg/day versus placebo for 15 days in a crossover design in 18 participants with an unknown family history of depression and found no effect on actual driving performance, psychomotor performance or visual memory performance. Paul and colleagues [Paul et al 2007] investigated escitalopram 20 mg/day versus placebo for 14 days in a crossover design in 24 participants with an unknown family history of depression and found no effect on psychomotor performance evaluated by multiple tests.…”
Section: Introductionmentioning
confidence: 99%